The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3732/ajb.1700008
|View full text |Cite
|
Sign up to set email alerts
|

Fire after a mast year triggers mass recruitment of slender mulga (Acacia aptaneura), a desert shrub with heat‐stimulated germination

Abstract: We attribute our findings to: (1) elevated soil temperatures during fires stimulating germination of heat-cued seeds; and (2) granivore satiation following masting facilitating assimilation of seeds into the soil seedbank. These results highlight the importance of rare seed-input events for regeneration in fire-prone systems dominated by masting plants, and provide the first example from an arid biome of fire interacting with masting to influence recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…It has also been noted that for some species the proximate causes triggering masting are also associated with an increased probability of natural fire disturbance, for example, stand aging and dead fuel accumulation in bamboo (Keeley & Bond, ), dry and hot spells in Norway spruce (Selås et al, ), European beech (Ascoli et al, ) and Dipterocarpaceae (Williamson & Ickes, ), or heavy rains followed by warm periods in Triodia spp. (Wright et al, ) and Acacia aptaneura (Wright & Fensham, ). Most of these authors have suggested that this positive feedback supports the ‘Environmental prediction hypothesis’ for mast seeding (Piovesan & Adams, ), which postulates the existence of traits that benefit plants in timing their seed crops using environmental cues to ‘predict’ which years will be favourable for seedling establishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been noted that for some species the proximate causes triggering masting are also associated with an increased probability of natural fire disturbance, for example, stand aging and dead fuel accumulation in bamboo (Keeley & Bond, ), dry and hot spells in Norway spruce (Selås et al, ), European beech (Ascoli et al, ) and Dipterocarpaceae (Williamson & Ickes, ), or heavy rains followed by warm periods in Triodia spp. (Wright et al, ) and Acacia aptaneura (Wright & Fensham, ). Most of these authors have suggested that this positive feedback supports the ‘Environmental prediction hypothesis’ for mast seeding (Piovesan & Adams, ), which postulates the existence of traits that benefit plants in timing their seed crops using environmental cues to ‘predict’ which years will be favourable for seedling establishment.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in fire‐prone regions of Australia found that seed production in grass and shrub species displaying heat stimulated seed germination ( Triodia spp. and Acacia aptaneura , respectively) was strongly related to increased fire likelihood in the 24 months after the reproduction event (Wright & Fensham, ; Wright et al, ). Similarly to our results for white spruce, in these studies the same climate cue (precipitation in previous months) was responsible for both the induction of flowering and the increase of burnt area, due to fuel build‐up and improved fuel connectivity after moist years.…”
Section: Discussionmentioning
confidence: 99%
“…In most other regions where the environment is under the influence of major climate modes, there is evidence that ecosystem processes respond to them, and it will be interesting to see how often that results in an alignment between drivers of seed production and other ecosystem processes improving reproductive fitness. For example, negative phases of ENSO, Indian Ocean Dipole (IOD) and Southern Annular Mode (SAM) concurrently modulate rainfall in central Australia, with direct effects on the productivity [59] and seed output [86][87][88][89] of mulga (Acacia sp.) and spinifex (Triodia sp.)…”
Section: Climate Modes Drive Synergies Between Masting and Reproductive Fitness Of Plantsmentioning
confidence: 99%
“…are triggered by heavy rainfall. This also promotes vegetation growth and increases fuel loads and connectivity across the landscape, increasing the likelihood of fires in temporal proximity with a masting event (figure 3) [43,44].…”
Section: (B) Indirect Interactionsmentioning
confidence: 99%